Teaching Russian Language in National Groups (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Teaching Russian in national groups is an important aspect of education that promotes cultural exchange, social integration and strengthening linguistic harmony. In diverse societies where different ethnic groups coexist, it is important to create conditions for the preservation and development of the linguistic heritage of each nation. Let's look at several key aspects of teaching Russian in national groups.